2016
DOI: 10.1016/j.ces.2016.03.012
|View full text |Cite
|
Sign up to set email alerts
|

Partial oxidation of methane on a nickel catalyst: Kinetic Monte-Carlo simulation study

Abstract: Kinetic Monte-Carlo simulation is applied to study the partial oxidation of methane over a nickel catalyst. Based on the Langmuir-Hinshelwood mechanism, the kinetic behavior of this reaction is analyzed and the results are compared with previous experiments. This system exhibits kinetic phase transitions between reactive regions with sustained reaction and poisoned regions without reaction. The fractional coverages of the adsorbed species and the production rates of H 2 , CO, H 2 O, and CO 2 are evaluated at s… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 36 publications
0
11
0
Order By: Relevance
“…The reaction mechanism has attracted increasing attention recently [15,16,[67][68][69]. The reaction may proceed through a combination of direct partial oxidation and steam reforming [39][40][41].…”
Section: Reaction Mechanismsmentioning
confidence: 99%
“…The reaction mechanism has attracted increasing attention recently [15,16,[67][68][69]. The reaction may proceed through a combination of direct partial oxidation and steam reforming [39][40][41].…”
Section: Reaction Mechanismsmentioning
confidence: 99%
“…2018 components of catalysts, relate to such promising methods [15][16][17][18][19]. The main advantages of these methods are: low energy costs, short synthesis times, no need for expensive equipment, the possibility of a onestage conversion of inorganic materials to final products using chemical reaction energy, an increase in non-stoichiometric phases of products due to high thermal gradient and rapid cooling rate [20][21][22].…”
Section: Introductionmentioning
confidence: 99%
“…In this simulation, lattice sizes of 64 × 64, 128 × 128, and 256 × 256 sites were examined under the same operating conditions, and it could be observed that the lattice size had no significant effect on the fractional coverages and rates of product formation, which is similar to the other works [34,[36][37][38]. Therefore, the lattice size of 64 × 64 sites was selected in this simulation study.…”
Section: Resultsmentioning
confidence: 59%
“…on the fractional coverages and rates of product formation, which is similar to the other works [34,[36][37][38]. Therefore, the lattice size of 64 × 64 sites was selected in this simulation study.…”
Section: Resultsmentioning
confidence: 71%
See 1 more Smart Citation